UPAYA PEMBERIAN EDUKASI PADA IBU HAMIL DALAM PENCEGAHAN STUNTING PADA BAYI - Rovica Probowati; Andriani Mei Astuti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Stunting is a health problem in Indonesia. The government in 2017 launched the program National Action Plan for handling stunting at the national, regional, especially village level. the program is wrong one of them is preventing stunting that occurs in the community. Because most people don't understand correctly regarding stunting, and assume that stunting or dwarfism is a term commonly used in society is a hereditary factor. The aim of this community service activity is to:increase knowledge and understanding as well as the role of pregnant women in prevention and detection programs It is hoped that early stunting in toddlers will directly motivate pregnant women to take part in ensuring this children receive good nutritional intake, especially during pregnancy up to 1000 days of age, as well as pay attention to the growth and development of their children so that their growth and development can be optimal. The method used is interactive lectures and questions and answers to pregnant women about prevention and how to assess/early detect stunting in toddlers using observation and data collection techniques pre-test with the aim of determining whether or not this educational activity is necessary. Analysis of pre-test and post data test to determine whether there is a change in understanding about prevention and how to assess/early detection stunting in toddlers. The results of educational activities for pregnant women in Selo Village, Boyolali Regency, have an effect on increasing pregnant women's understanding of prevention and how to assess/early detection of stunting in toddlers.